FAKTOR-FAKTOR YANG MEMPENGARUHI MINAT BELI PAKAIAN SYAR’I (STUDI KASUS MAHASISWI UIN ANTASARI BANJARMASIN) - Eka Sri Apriliana (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2019)
This research analyzes factors that influence the buying interest of female students in sharia clothing, namely price, trends and religiosity. This research was conducted with a quantitative approach with the sampling technique used is proportional stratified sampling. The research data obtained were analyzed using the Multiple Liner Regression Analysis technique with the help of the SPSS version 22 program. This study produced findings: First: the independent variables in this study consisted of price (X1), trend (X2) and religiosity (X3) simultaneously influences the buying interest (Y) of syar'i clothing for female students of UIN Antasari Banjarmasin with a Fcount value of 67.900 greater than the Ftable value of 1.19 (67.900> 1.19) and a significant F value of 0.000 less than an α value of 0 , 05 (0,000 <0.05) while partially each of the three variables, namely the price variable (X1), trend (X2) and religiosity (X3) affect the interest in buying sharia clothes in UIN Antasari Banjarmasin students. Second: religiosity is the most dominant variable partially influencing the buying interest of shari'a clothing for students of UIN Antasari Banjarmasin in accordance with the t test, this is evidenced from the unstandardized coefficients of 0.467 and standardized coefficients of 0.503 and a sig level of 0.000.